Remote ischaemic conditioning in the context of type 2 diabetes and neuropathy: the case for repeat application as a novel therapy for lower extremity ulceration. Issue 1 (December 2016) - Epps, J.; Smart, N.
Abstract An emerging treatment modality for reducing damage caused by ischaemia–reperfusion injury is ischaemic conditioning. This technique induces short periods of ischaemia that have been found to protect against a more significant ischaemic insult. Remote ischaemic conditioning (RIC) can be administered more conveniently and safely, by inflation of a pneumatic blood pressure cuff to a suprasystolic pressure on a limb. Protection is then transferred to a remote organ via humoral and neural pathways. The diabetic state is particularly vulnerable to ischaemia–reperfusion injury, and ischaemia is a significant cause of many diabetic complications, including the diabetic foot. Despite this, studies utilising ischaemic conditioning and RIC in type 2 diabetes have often been disappointing. A newer strategy, repeat RIC, involves the repeated application of short periods of limb ischaemia over days or weeks. It has been demonstrated that this improves endothelial function, skin microcirculation, and modulates the systemic inflammatory response. Repeat RIC was recently shown to be beneficial for healing in lower extremity diabetic ulcers. This article summarises the mechanisms of RIC, and the impact that type 2 diabetes may have upon these, with the role of neural mechanisms in the context of diabetic neuropathy a focus. Repeat RIC may show more promise than RIC in type 2 diabetes, and its potential mechanisms and applications will also be explored. Considering the high costs, rates of chronicity and serious complications resulting from diabetic lower extremity ulceration, repeat RIC has the potential to be an effective novel advanced therapy for this condition.